Hospice quality of care in home vs. assisted living facility vs. nursing home settings - Unroe, Kathleen T. (J Am Geriatr Soc, 2018)
OBJECTIVES: To describe differences in perceived quality of hospice care for patients living in home, nursing home or assisted living facility settings through analysis of after-death surveys of family members. DESIGN: Retrospective cohort study using hospice medical record data and Family Evaluation of Hospice Care (FEHC) survey data. SETTING: Large, national hospice provider. PARTICIPANTS: Patients who died while receiving routine hospice care and family caregivers who completed after-death quality of care surveys. MEASUREMENTS: Survey results for 7,510 patients were analyzed using analysis of variance and chi-square tests. Logistic regression was used to assess relationship between location of care and overall service quality. RESULTS: The overall survey response rate was 27%; 34.5% of families of assisted living hospice patients returned the survey vs 27.4% for home and 22.9% for nursing home patient (p<.0001). A majority, 84.3%, of respondents reported that the timing of hospice referral had occurred at “the right time.” Overall, 63.4% of respondents rated service quality as “excellent.” Hospice care in the nursing home was less likely to be perceived “excellent.” Differences in return rate by primary diagnoses were significant, although differences were not large. CONCLUSION: There were significant differences in the characteristics of patients whose family members did and did not return surveys which has implications for increased use of after-death surveys to evaluate hospice quality. Lower perceived quality of hospice care in nursing homes may be related to general dissatisfaction with receiving care in this setting. Survey results have the potential to set priorities for quality improvement, patient choice of provider, and potentially reimbursement. Underlying causes of differences of perceived quality in different settings of care should be examined.